PENGARUH KEPEMIMPINAN, KEDISIPLINAN, DAN LINGKUNGAN KERJATERHADAP PRESTASI KERJA GURU - Jihan Suci Lestari; Umi Farida; Siti Chamidah (Universitas Muhammadiyah Ponorogo, 2020)
This study aims to determine the effect of leadershipt, discipline, and work environment on teacher work performanceat SMAN 1 Dagangan. The research method in this study uses quantitative methods. The population in this study were all teachers of SMAN 1 Dagangan totaling 53 teachers. The sampling method used is sampling jenuh , which is taking sample members from a population with a population that is relatively small, the sample was 53 teachers from 50 populations. Data collection methods in this study are primary data and secondary data. Testing instruments using validity test, and reliability test. While for data analysis using multiple linear regression analysis, and hypothesis testing using t test and f test. The results of the study show that: (1) leadership has a positive effect (0,427) and significant on teacher work performanceat SMAN 1 Dagangan, (2) Discipline has a positive effect (0,312) and significant on teacher work performanceat SMAN 1 Dagangan, (3) work environment has a positive effect (0,250) and significant on teacher work performanceat SMAN 1 Dagangan.